VISION SYSTEMS OF UAVs AND SIMULATION OF OBJECT RECOGNITION IN MATLAB ENVIRONMENT (World Science, 2023)
In recent years, we are aware of the increase in the production of unmanned aerial vehicles (UAVs), their application in various fields and their future potential. An unmanned aerial vehicle (UAV) is an aircraft without a crew. UAVs can have variable characteristics: they can be remotely piloted or fully automatic. In these articles, we will consider UAVs, which we consider as dynamic objects, to receive the coordinates of ground objects according to their flight modes, to simulate them, to observe them, to draw their images, and to classify the objects in the image according to various characteristics in real time. Among the researches of recent times, the researches related to the detection of moving or stationary objects from real-time images taken from unmanned vehicles are of special importance. Because continuous surveillance cannot be done with old video surveillance systems. Integration with systems that automatically detect and recognize objects is used for continuous monitoring.